Organ donation in peru and its associated demographic factors - Chaquila , José A. (2025)
The sociodemographic factors associated with organ donation in Peru during 2023 were determined through a secondary analysis of the open database of the National Registry of Identification and Civil Status (RENIEC). The covariates were sex, age, area of residence, and macro-region. Poisson regression was used to evaluate the associations. A total of 13.1% were donors. There was a lower prevalence of donation among men (RPa: 0.94, 95% CI: 0.94 - 0.95). The prevalence of donation was 19% lower among older adults compared to the 18-30 years age group (RPa: 0.81, 95% CI: 0.80 - 0.81). Belonging to a rural area decreased the probability of donation by 62% compared to urban areas (RPa: 0.38, 95% CI: 0.38 - 0.38). The prevalence of organ donation in Peru was low. The groups with the lowest probability of donation were males, older adults, and rural inhabitants.